STUDI PENGGUNAAN KAPUR SEBAGAI BAHAN ADITIF TERHADAP KARAKTERISTIK CAMPURAN BETON ASPAL LAPIS AUS (AC-WC) - Mansyur, Kartini; Mashuri, Mashuri; Alhadar, Ali (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Asphalt Concrete Wearing Course (AC-WC) is the layer indirect contact with the wheels of the vehicle that makes this layer is easy damage. The use of additive in Asphalt Concrete Mixtures as AC-WC has often done to improve the durability. One of additional material that has been used is hydrate lime. The aim of this research was to know the effect of using lime as additive on AC-WC characteristics.Variations lime used in this study was 0%, 5%, 10%, 15%, 20%, 25% respectively. Characteristic of AC-WC mixture include stability, flexibility, durability, VIM, VMA, VFB and flow of the mixtures. Test characteristic of the mixtures using Marshall Method.Analysis of the relationships the characteristic of AC-WC mixtures with variations of lime using statistical methods is experiment factorial at 95% confidence level or Î±= 5%. The result of this study was to found that using lime as additives to effect the characteristic of AC-WC mixtures. Optimum Asphalt Content tends to increase due to increased lime content in the AC-WC. The result also found that the best lime content is 15%, Optimum asphalt content is 6.67% with an increase stability value of 9.75%, durability value of 1.39% and flexibility value of 11.61% when compared to the characteristics of AC-WC mixture without additives lime.Keyword:Â Lime, Asphalt Concrete Wearing Course (AC-WC)